Integrating ChatGPT Into Clinical Laboratory Science Education: A Survey and Pilot Study. - ZHENG, YAN; ZHU, WENXIANG; CARPENTER, ALEXIS N. B. (Clinical Laboratory Science)
Artificial intelligence (AI) holds significant potential to transform higher education, including health professions education. ChatGPT, a large language model, is reshaping teaching and learning within this field. This study explores the impact of ChatGPT on clinical laboratory science (CLS) education by examining the knowledge, perspectives, and experiences of learners from the CLS and Doctorate in Clinical Laboratory Science (DCLS) programs. A cross-sectional survey assessed learners' knowledge, attitudes, and use of ChatGPT, and a ChatGPT/AI-assisted learning module was integrated into the CLS/DCLS curricula to evaluate its practical application. The results revealed that CLS learners were significantly more familiar with and used ChatGPT more frequently in their coursework compared with DCLS learners. However, DCLS learners expressed greater optimism about integrating ChatGPT/AI into both professional education and clinical practice. Key concerns raised by both groups included academic integrity and the accuracy of ChatGPT's outputs. Although learners recognized ChatGPT's potential to assist with research, scientific writing, and learning support, they also emphasized the importance of human oversight to mitigate biases stemming from limited training data. Despite these concerns, over half of the respondents expressed a positive outlook on ChatGPT/AI, anticipating its valuable role in future clinical laboratory practice. This study highlights the need for careful AI integration to address risks while maximizing educational benefits. Establishing clear guidelines and policies is essential for educators to leverage ChatGPT/AI effectively, ensuring ethical use and maintaining academic integrity in health professions education.